Vigilantism among the Community in Aceh Against the Accused of Violating the Shariah Criminal Law - Faisal Husen Ismail; Jasni Sulong; Zaitun Muzana; Sabirin; Arwanyah Bin Kirin (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2022)
This article aims to study triggering factors to make vigilantism against perpetrators of jinayat sharia law violation in Aceh and analyze vigilantism based on the same law. This qualitative research uses literature study and field research as the approach methods. Relevant books, journals, newspapers, and laws and regulations are the primary references while the field study was conducted by interviewing respondents from Islamic criminal law enforcement officers in Aceh. This study found that the emotional attitude of the community, the attitude of joining in, the length of the trial process, the experience of freeing the perpetrators from punishment, and fights between the community and the perpetrators are factors that encourage people to take vigilante actions. The research also found that the punishment of being married off, being bathed in dirty water, as well as beating the accused before being tried in the court were acts that violated the procedures for the Aceh criminal law (Qanun Jinayat). It thus recommends further research related to the reflection of the implementation of Qanun Jinayat in Aceh for the sake of achieving the purpose beyond the qanun.